Anxiety in elite young gymnasts:part I - Definition of stress and relaxation - Duda, J. L.; Gano-Overway, L. (Technique, 1996)
The world of high-level gymnastics is characterized by intensive practice demanding competition, the public display of skills, and evaluation by others. This environment may be overwhelming for gymnasts of all ages but less is known about the nature, determinants, and effects of anxiety for the serious, young competitor. How such athletes view and respond to stress in some ways will determine their success in gymnastics as well as the quality of their gymnastics experience. Competitive stress is defined as the "negative emotions, feelings, and thoughts that one might have with respect to their [athletic] experience such as feelings of apprehension, anxiety, muscle tension, nervousness, physical reaction, thoughts centered on worry and self-doubt, and negative statements" (Scanlan, Stein, and Ravizza, 1991, p. 105). These feelings and emotions arise from an imbalance between athletes' perceptions of their abilities and the perceived demands of the situation (Martens, 1987). In essence, competitive stress is an individualized process that is greatly due to how each athlete perceives his/her sport world. It is the purpose of this first article in a series to examine the personal definitions of stress among young gymnasts to learn more about their anxiety responses. To provide a potential telling contrast, definitions of the relaxation state were also explored. Knowledge of such subjective definitions is critical if we hope to maximize skill development and maintain the involvement of young talented gymnasts. Sport psychology research has demonstrated that competitive stress leads to performance decrements, a greater likelihood of injuries, and more attentional difficulties (Beuter and Duda, 1985; Burton, 1988; Williams, Tonymon and Anderson, 1991). Studies have also shown that anxiety corresponds to decreased enjoyment and higher dropout rates (Smith, 1986). Consistent with this literature, an examination of TOP Team members' perceptions of stress revealed this experience to be an unpleasant and undesirable state that is manifested in the way they think, feel, and act. This finding informs us that young, elite gymnasts are conscious of what stress is like within their athletic environment. Stress was especially associated with fearful and/or frustrating emotional reactions to what was required in the sport. Based on their responses, it was apparent that the current sample of gymnasts did not view being anxious as conducive to optimal performance or related to a quality gymnastics experience. The members of the TOP Team were also cognizant of the contrasting, positive dimensions associated with relaxation. They viewed relaxation as marked by affirming thoughts, good feelings and, in particular, a desirable condition in terms of their bodies. These results are also aligned with the sport psychology literature which suggests that relaxation is "a relaxed state of mind which prepares the performer to produce more effectively than if it were in a slightly tensed state, just as a relaxed muscle can contract more effectively than a slightly tensed one" (Kubistant, 1986 p. 126). Thus, when a gymnast is relaxed, it should facilitate her concentration, help conserve energy and assist the athlete in controlling minute aspects of her performance.